Migratory connectivity and effects of winter temperatures on migratory behaviour of the European robin Erithacus rubecula: a continent‐wide analysis. (1st March 2016) - Ambrosini, Roberto; Cuervo, José Javier; du Feu, Chris; Fiedler, Wolfgang; Musitelli, Federica; Rubolini, Diego; Sicurella, Beatrice; Spina, Fernando; Saino, Nicola; Møller, Anders Pape
Summary: Many partially migratory species show phenotypically divergent populations in terms of migratory behaviour, with climate hypothesized to be a major driver of such variability through its differential effects on sedentary and migratory individuals. Based on long‐term (1947–2011) bird ringing data, we analysed phenotypic differentiation of migratory behaviour among populations of the European robin Erithacus rubecula across Europe. We showed that clusters of populations sharing breeding and wintering ranges varied from partial (British Isles and Western Europe, NW cluster) to completely migratory (Scandinavia and north‐eastern Europe, NE cluster). Distance migrated by birds of the NE (but not of the NW) cluster decreased through time because of a north‐eastwards shift in the wintering grounds. Moreover, when winter temperatures in the breeding areas were cold, individuals from the NE cluster also migrated longer distances, while those of the NW cluster moved over shorter distances. Climatic conditions may therefore affect migratory behaviour of robins, although large geographical variation in response to climate seems to exist. Abstract : To assess the response of animal populations to changing climate, we need long time series of data. Ringing data are an invaluable tool for such analyses. They show that climatic conditions affect migratory behaviour of the European robin determining a reduction in migration distance and a shift in their wintering grounds.